The Role of Adolescent Health Services in Promoting Sexual Health in Indonesia - Fitri, Rahmi Pramulia; Syafriani, Syafriani; Oktaviani, Yoneta (Journal of Health and Nutrition Research, 2025)
Adolescents are a population group vulnerable to various reproductive health risks due to limited access to accurate sexual health information and youth-friendly services. This study aims to explore the role of adolescent health services in promoting sexual health among adolescents. Using a narrative literature-policy review, the analysis was based on current literature and policy reviews regarding adolescent health promotion in Indonesia. The findings indicate that adolescent health services play a significant role in increasing awareness, knowledge, and preventive behaviors related to sexual and reproductive health. Key strategies include the provision of youth-friendly service facilities, health education using appropriate media, and peer counseling. However, various challenges such as lack of trained personnel, stigma in society, and limited adolescent participation hinder service effectiveness. This study emphasizes that in Indonesia, the need for multi-sector collaboration, improvement of health personnel competence, and the involvement of adolescents in the design of educational programs. Strengthening the capacity and accessibility of adolescent health services is crucial in Indonesia to improving the overall sexual health status of adolescents and preventing reproductive health problems at an early age.